Traffic online ads design through Advertising effectiveness “A case of online banner ads on the Tribun Bali website page” - Berlian, Christian Wahyu (Universitas Pendidikan Nasional, 2021)
Advertising has a very important role in achieving a company's goals. Of course, the advertising made by the company must be effective so that the purpose of the advertisement is made to the public and right on target. There are many factors that affect the effectiveness of advertising such as the stimulus of advertising, advertising messages, and advertising media. The purpose of this study is to examine the effect of Advertising Stimulus, Advertising Messages, and Advertising Media on Advertising Effectiveness. The object of this research is the TribunBali website and the number of respondents in this study is 120 people. In data processing, data is processed using SPSS and the results of data processing show that Advertising Stimulus has a positive influence on Advertising Effectiveness, Advertising Messages have a positive effect on Advertising Effectiveness and Advertising Media has a negative effect on Advertising Effectiveness. Based on the results of the analysis, to be able to produce an advertisement that has high effectiveness, namely by paying attention to the advertising stimulus in the ad and paying attention to the advertising message that will be delivered in the advertisement. Meanwhile, the selection of advertising media for the research object is not effective.